Kajian tentang Program Bimbingan dan Konseling untuk Anak Usia Dini - Zulfa, Mona Yulia (Sekolah Tinggi Ilmu Tarbiyah (STIT) Syekh burhanuddin, 2023)
The guidance and counseling (BK) program is a program that must exist in educational units, especially in PAUD, because it can make it easier for PAUD teachers or assistants to provide learning materials. This research is based on the limitations of PAUD teachers or assistants in understanding, compiling and realizing BK programs for early childhood. The aim of this research is to map the concept of the BK program for early childhood which has been carried out by existing studies and can be a basic guide for PAUD teachers or assistants in developing a BK program that is integrated with learning. The method used is a qualitative literature study method, by analyzing several books and previous research collected through online tools such as